Argentina, Chile and the Joint Antarctic Naval Patrol: a successful confidence building mechanism. Issue 1 (2nd January 2017) - Sanchez, W. Alejandro
Abstract: Established in the late 1990s, the Joint Antarctic Naval Patrol (PANC) is a defence initiative that brings together naval platforms from Argentina and Chile to monitor Antarctic waters and territory. After almost 20 annual campaigns, Patrol vessels have helped numerous vessels in need, as well as having carried out an emergency extraction from a Brazilian base in 2012. The success of the PANC is even more commendable given the occasionally tense relations between Argentina and Chile, which include overlapping Antarctic claims. The PANC is likely to continue operating for the immediate future particularly since climate change, which translates into a longer Antarctic summer, and greater maritime traffic has already prompted recent campaigns to extend operations for an additional two weeks. Nevertheless, one factor that hinders the Patrol and its capabilities is that it is made up of a few ageing vessels, and neither Argentina nor Chile have recently obtained modern platforms for Antarctic operations. In spite of this limitation, the activities carried out by these two navies make the PANC an example of how military cooperation to protect the Antarctic and human activities there is possible.